The role of ATF4 in hypoxia-induced cell death in cancer - Pike, L; Luke R.G. Pike (2011)
Cancer cells survive the harsh oxygen and nutrient deprivation of the tumour microenvironment through the selection of apoptosis-resistant and glycolytic clones (Cairns et al., 2011; Graeber et al., 1996). In particular, the integrated stress response (ISR) has been shown to be pivotal in cancer cell survival in vivo and the resistance of cancer cells to therapy (Harding et al., 2003). In recent years, it has become apparent that increased autophagy is one mechanism by which the ISR can confer resistance to stress (Kroemer et al., 2010). ATF4 is a major transcriptional effector of the integrated stress response in severe hypoxia (<0.01% O₂). ATF4 is a well-established regulator of genes involved in oxidative stress, amino acid synthesis and uptake, lipid metabolism, protein folding, metastasis, and angiogenesis. Recent work has demonstrated an important role of ATF4 in promoting resistance to severe hypoxia through the transcriptional upregulation of MAP1LC3B and ATG5, essential components of the autophagy machinery (Rouschop et al., 2009b; Rzyski et al., 2010). In this work, the author describes several novel ATF4 target genes, and examines their role in the regulation of autophagy and the resistance of cancer cells to severe hypoxia. In the first part of this thesis, the author shows that three BH3-only members of the BCL-2 family of proteins--HRK, PUMA, and NOXA--are upregulated in response to severe hypoxia in an ATF4-dependent manner. In particular, the author shows that the poorly described BH3-only protein HRK is a direct target of transcriptional activation by ATF4, and that HRK induces autophagy in severe hypoxia, thereby providing the first evidence that the integrated stress response can transcriptionally trigger the autophagy process. In contrast to the previously described role of HRK in apoptosis, this thesis demonstrates that HRK can play a pro-survival role in the context of breast cancer cells. In the latter part of this thesis, the author identifies the essential autophagy gene ULK1 as an ISR target. The author shows that ULK1 expression in severe hypoxia is transcriptionally upregulated through direct activation by ATF4. The author identifies ULK1 as a crucial regulator of autophagy and mitophagy in both normoxia and severe hypoxia and shows that ULK1 plays a pivotal role in cancer cell survival. Furthermore, it is shown that human breast cancer patients with high levels of ULK1 relapse earlier than those with low levels of ULK1, thereby identifying ULK1 as a potential target for cancer therapy.